Wire Cerclage Versus Cable Closure After Sternotomy for Dehiscence and DSWI: A Systematic Review and Meta-Analysis. Issue 4 (July 2020) - Dixit, Apurva; Tam, Derrick Y.; Yu, Monica; Yanagawa, Bobby; Gaudino, Mario; Lam, Tiffany; Fremes, Stephen E.
Objective: Cable closure has been introduced as a potential alternative to traditional wire cerclage (WC) for closure of median sternotomy. To evaluate whether cable closure improves patient outcomes, we conducted a systematic review and meta-analysis of the literature. Methods: Ovid versions of Medline and Embase, and Google Scholar were used for the literature search. This yielded 7 studies ( n = 2, 758), which compared traditional WC to cable closure systems. Outcomes included deep sternal wound infection, sternal dehiscence, postoperative pain score, and sternal wound infection. Results: We found significantly lower incidence of sternal dehiscence for cable closure compared to WC (risk ratio [RR] 0.14, 95% confidence interval [CI]: 0.03 to 0.59, P < 0.01, I 2 = 0%) but no difference in DSWI (RR 0.97, 95% CI: 0.39 to 2.42, P = 0.95, I 2 = 33%). Cable closure was also associated with lower pain when compared with the WC group (mean difference −1.04 points, 95% CI: −1.89 to −0.19, P = 0.02, I 2 = 87%). Conclusions: This study suggests that cable closure results in less incidence of sternal dehiscence and pain compared to WC. Nonetheless, there remains a limited number of studies on this topic and further high-quality studies are required to confirm the results of this meta-analysis.